Pola Program Berpikir Kritis (Critical Thinking) dalam Ruang Belajar Mengajar Era Abad 21 (Studi pada Pasraman Kota Tangerang) - Iluh Junia Eka; I Made Awanita; I Ketut Angga Irawan (Jurnal PASUPATI, 2020)
This thesis discusses Critical Thinking Patterns in the 21st Century Era of Teaching and Learning Space (Studies in Pasraman, Tangerang City). The purpose of this study is to find out how the pattern of Critical Thinking Program (critical thinking) in teaching and learning space and What are the Positive and Negative Impacts of Teaching and Learning Process Using Critical Thinking. This research is a qualitative research with a descriptive design. Data collection techniques using research instruments, interviews, observation and documentation. The author conducted interviews with informants. The results of the study prove that the critical thinking program pattern in the 21st century teaching and learning space in Pasraman Kerta Jaya Tangerang and Pasraman Dharma Sidhi Ciledug, that the critical thinking program pattern has begun to be applied in Pasraman Kerta Jaya Tangerang and Pasraman Dharma Sidhi Ciledug. The positive and negative impacts of training the ability of Hindu young generation to become a generation of good leaders in the future and carry a better Hindu name.Keywords : Critical thinking, 21st Century Era